1980
DOI: 10.1002/jcp.1041040110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of RNA synthesis and passage of chick embryo fibroblasts through the G1 period

Abstract: Events that are essential for progression through the G1 period begin immediately or shortly after resting chick embryo cells are given fresh medium with serum. The following observations support the contention that the critical events include the production of non-ribosomal RNAs: (1) Addition to the "shift-up" medium of either of two inhibitors of RNA formation, camptothecin or 5, 6-dichloro--1-beta-D-ribofuranosylbenzimidazole, delays the onset of DNA replication by about the length of time the cells are exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This same fraction could not enter the S phase i which quiescent when given 10% serum plus DRB. DRB also delayed Gl imulated near the transit by chicken embryo fibroblasts (5). Inhibitor studies of i-free medium for quiescent, serum-starved murine AKR-2B cells have similarthen shifted into ly shown that hnRNA synthesis is required for entry into the in Fig.…”
Section: Downloaded Frommentioning
confidence: 91%
“…This same fraction could not enter the S phase i which quiescent when given 10% serum plus DRB. DRB also delayed Gl imulated near the transit by chicken embryo fibroblasts (5). Inhibitor studies of i-free medium for quiescent, serum-starved murine AKR-2B cells have similarthen shifted into ly shown that hnRNA synthesis is required for entry into the in Fig.…”
Section: Downloaded Frommentioning
confidence: 91%
“…Growth curves with hu IFN-a were essentially the same except that the cells were less sensitive. It has been shown that cell lines accumulating in GdG, at high density are IFN-sensitive (Creasey et al, 1980). U-251 MG could be synchronized by serum starvation at Go.…”
Section: A Ntiproli Ferati Ve Effectmentioning
confidence: 99%
“…DRB prolonged the intermitotic interval in cells cycling in the presence of the drug, but the effect was less in 15% than in 5% serum. After prolonged treatment of HeLa cells with DRB, the inhibition of heterogeneous nuclear RNA synthesis by DRB appeared to be reduced, which was not due to inactivation of DRB in the culture medium.The /&linked D-riboside of 5,6-dichlorobenzimidazole (DRB) (1-3) has been shown to inhibit the proliferation of animal cells in culture (1,4,5). In diploid human fibroblasts, the inhibition of cell proliferation appears to be reversible upon removal of DRB (5).…”
mentioning
confidence: 99%
“…The /&linked D-riboside of 5,6-dichlorobenzimidazole (DRB) (1-3) has been shown to inhibit the proliferation of animal cells in culture (1,4,5). In diploid human fibroblasts, the inhibition of cell proliferation appears to be reversible upon removal of DRB (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation